Androgen receptor inhibitor ameliorates pulmonary arterial hypertension by enhancing the apoptosis level through suppressing the Notch3/Hes5 pathway - Sun, Jiayan; Lin, Jiancheng; Yin, Di; Pan, Zetao; Ye, Yuheng; Wang, Yi; Wang, Xiaowan; Guo, Qiang (Frontiers in Pharmacology, 2025)
BackgroundPulmonary arterial hypertension (PAH) exhibits significant gender differences in prognosis, with male patients typically showing worse outcomes than females. These disparities may stem from differences in androgen receptor expression and activity. Clinical studies suggest that the androgen receptor plays a crucial role in the pathophysiology of PAH, influencing disease progression and treatment response. Despite the lack of targeted therapies for PAH, these findings have spurred investigations into the potential therapeutic role of androgen receptors. This study explores the role of androgen receptors in PAH and evaluates their therapeutic potential.MethodsPAH was induced in rats via intraperitoneal injection of monocrotaline (MCT). Following model establishment, Enzalutamide was administered every 3 days at 10 mg/kg once for a total of 7 times (21 days). A mouse model of PAH was developed by subcutaneously injecting SU5416 and exposing the mice to hypoxia. Androgen receptor knockout (AR−/−) mice were also utilized to investigate the role of androgen receptors in disease progression. Key indicators were compared across groups. The in vivo mechanisms through which androgen receptors influence PAH were examined in both rat and mouse models. Additionally, mouse pulmonary artery endothelial cells (PAECs) were cultured under hypoxic conditions to create an in vitro model of PAH, facilitating further investigation into the role of androgen receptors in disease pathogenesis.ResultsCompared to the normal group, the model group exhibited significantly increased androgen receptor expression in rats, mice, and mPAECs. This was accompanied by pronounced pulmonary artery wall thickening, right ventricular hypertrophy, pulmonary fibrosis, elevated pulmonary artery pressure, and a reduced level of apoptosis both in vivo and in vitro. Furthermore, activation of the Notch3/Hes5 signaling pathway was observed. However, treatment with androgen receptor inhibitors or gene knockout significantly ameliorated these pathological changes. Apoptosis levels increased both in vivo and in vitro, and the activation of the Notch3/Hes5 signaling pathway was effectively inhibited.ConclusionOur findings suggest that in both animal models and the hypoxic mPAECs, inhibition of androgen receptor expression leads to increased apoptosis via suppression of the Notch3/Hes5 signaling pathway. This mechanism likely contributes to the therapeutic effects observed, providing insights for potential treatment strategies targeting androgen receptors in pulmonary arterial hypertension.